2021
DOI: 10.1007/s11207-021-01866-6
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Features of Diurnal Variation of Galactic Cosmic Rays

Abstract: We analyze the scaling properties of the diurnal variation of galactic cosmic rays (GCRs) in Solar Cycle 24 and the solar minima between Solar Cycles 23/24 and 24/25 for 2007 – 2019 based on the count rates of the Oulu, Newark, Hermanus, and Potchefstroom neutron monitors. The scaling features of the GCR diurnal variation are studied by evaluating the Hurst exponent, a quantitative parameter used as an indicator of the state of the randomness of a time series. We estimate the Hurst exponents for GCR diurnal-va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In this work, basing on the review of literature and continuing our previous studies [32,45], we initially compared a few methods: the Katz algorithm [11], which revealed discriminating power [32,38], its modifications [46,47], Higuchi method [12], Structure Function scaling [18,[48][49][50], and Detrended Fluctuation Analysis [15,51].…”
Section: Fractal Methods Selectionmentioning
confidence: 99%
“…In this work, basing on the review of literature and continuing our previous studies [32,45], we initially compared a few methods: the Katz algorithm [11], which revealed discriminating power [32,38], its modifications [46,47], Higuchi method [12], Structure Function scaling [18,[48][49][50], and Detrended Fluctuation Analysis [15,51].…”
Section: Fractal Methods Selectionmentioning
confidence: 99%
“…Kumar (1998) revealed that a shift to early hours during specific periods is related to the polarity of the solar magnetic field, Park (2018) confirming a 22-year periodicity. The studies of (Modzelewska et al, 2021;Park, 2018) have shown that the diurnal phase tends to shift towards later hours during the maximum solar activity years compared with the minimum solar activity years. Furthermore, Okiyi et al (2017) suggested that phase variation has components of both 22-year and 11-year cycles, influenced by solar polar magnetic field reversal and interplanetary magnetic field strength changes associated with sunspot cycles.…”
Section: Background and Literature Surveymentioning
confidence: 99%
“…More recently, Pavlos et al (2019) employed Hurst analysis for the study of the energetic ion intensity and magnetic field for the description (and understanding) of small-scale magnetic island structures in the solar wind of typical size 0.01-0.001 au at 1 au. The Hurst method was recently applied by Modzelewska et al (2021) in the study of galactic cosmic rays based on data obtained by the Oulu, Newark, Hermanus, and Potchefstroom neutron monitors. To understand the processes in the near-Earth electromagnetics, the Hurst exponent, together with other complex system methods, has also been reviewed by Balasis et al (2023).…”
Section: Introductionmentioning
confidence: 99%